(untitled) (Research, Society and Development, 2023)
Introduction: The health system had to be restructured to meet the demands arising from the pandemic. This situation reverberated in the mental health of professionals in specialized services, already overloaded and subjected to precarious labor relations. Objective: This study aims to analyze the influence of the work process on the mental health of workers at a Psychosocial Care Center II – CAPS in a municipality in Ceará. Methodology: This is qualitative research using semi-structured interviews carried out in December 2022 with 12 professionals. The collected data were transcribed and analyzed using the Thematic Content Analysis technique. Results: The work context can generate suffering/illness for workers who are overloaded due to lack of human and material resources. Based on the interviewees’ reports, there is no implementation of the National Policy for the Valorization of Male and Female Workers and no spaces for mental health care for professionals. Conclusion: It is necessary to plan actions for mental health care, which should start from local management. In addition, understanding that the way of organizing health care, as municipal management, impacts on the health of professionals.